2013
DOI: 10.1093/cercor/bht103
|View full text |Cite
|
Sign up to set email alerts
|

Musicians' Enhanced Neural Differentiation of Speech Sounds Arises Early in Life: Developmental Evidence from Ages 3 to 30

Abstract: The perception and neural representation of acoustically similar speech sounds underlie language development. Music training hones the perception of minute acoustic differences that distinguish sounds; this training may generalize to speech processing given that adult musicians have enhanced neural differentiation of similar speech syllables compared with nonmusicians. Here, we asked whether this neural advantage in musicians is present early in life by assessing musically trained and untrained children as you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 82 publications
6
103
1
3
Order By: Relevance
“…These findings therefore provide support for the efficacy of community and co-curricular music programs to engender improvements in nervous system function. These children are from underserved backgrounds and stand at high risk for academic and social problems; this impoverishment carries concomitant biological insults (Bradley and Corwyn, 2002;Skoe et al, 2013). Our finding reveals the potential for neuroplasticity in the impoverished human brain (Neville et al, 2013), paralleling an effect shown in a rat model (Zhu et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…These findings therefore provide support for the efficacy of community and co-curricular music programs to engender improvements in nervous system function. These children are from underserved backgrounds and stand at high risk for academic and social problems; this impoverishment carries concomitant biological insults (Bradley and Corwyn, 2002;Skoe et al, 2013). Our finding reveals the potential for neuroplasticity in the impoverished human brain (Neville et al, 2013), paralleling an effect shown in a rat model (Zhu et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…This interpretation is supported by evidence from humans and animals that the nervous system has profound potential for functional reorganization following auditory training, imparting a positive impact on everyday communication (Recanzone et al, 1993;Blake et al, 2006;Kilgard, 2012;Anderson et al, 2013;Anguera et al, 2013;Heim et al, 2013;Engineer et al, 2014). It is thought that music training can effect structural and functional neural changes (i.e., experience-dependent plasticity; Kraus and Chandrasekaran, 2010;Patel, 2011;Herholz and Zatorre, 2012;Zatorre, 2013) because music engages widely distributed sensory, cognitive, and reward networks in the brainthe very networks whose integration drives neuroplasticity.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Relatedly, the modality-specificity or generality of these effects remains unclear. While some work suggests that musician advantages in EF (and other cognitive abilities) may be limited to auditory tasks (e.g., Hansen, Wallentin, & Vuust, 2013;Strait et al, 2010;Strait, O'Connell, Parbery-Clark, & Kraus, 2014;cf. Carey et al, 2015), other studies find effects in the visual modality as well (e.g., Bialystok & DePape, 2009;Oechslin et al, 2013), but there have been few investigations using comparable auditory and visual EF tasks.…”
Section: Introductionmentioning
confidence: 99%
“…differentiate speech sounds to a greater extent (65)(66)(67), track stimulus pitch more accurately (68,69), and are more consistent across trials (59,70). In adolescence, music training leads to faster responses to speech in noise (71), but the extent to which adolescent music training can confer other aspects of the musician signature remains unknown.…”
mentioning
confidence: 99%